Tvorba mikroklimatu průmyslové haly s vysokými nároky na jeho rovnoměrnost - Tůmová, Eliška (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Diplomová práce se zabývá optimalizací mikroklimatu v průmyslové hale, kde je pro výrobu požadována stálá teplota s minimálními výkyvy. Při nedostatečném výkonu dílčí klimatizace bylo cílem navrhnout řešení, které zajistí stálost vnitřní teploty při provozu zejména pro letní období a bude ekonomicky přijatelné. Simulace původního stavu prokazuje definované problémy. Experimentálním měřením a srovnávací metodou jsou v práci zhodnoceny některé nové či pro stínění netradiční materiály. Každému materiálu je přiřazen stínící součinitel, čímž je dosaženo univerzálnosti ve výpočtu tepelných zisků vznikajících slunečním zářením. Součástí experimentů a jejich zhodnocení je určení tloušťky skla standardního jednoduchého zasklení. Dále je určena poměrná propustnost pro některé vícekomorové polykarbonáty, které jsou v současnosti používané jako výplň průmyslových světlíků i okenních otvorů výrobních hal. Z experimentů vyplývající návrh je podroben simulaci. Po instalaci navrženého stínění je uvedeno srovnání průběhu teplot v zadaném objektu před provedení úprav a po něm.

This diploma thesis deals with the optimization of microclimate of an industrial building. There is required constant temperature with minimal fluctuations during manufacturing process in the building. Due to insufficient cooling power of air-conditioning system was objective to design a solution that ensures stability of internal temperature during production especially in summer and simultaneously should be the solution economically acceptable. Simulation shows original state defined problems. Some new or unusual materials for solar shading are reviewed in the thesis by the experimental measurements and by the comparative method. To each material is assigned shading coefficient according to Czech standards, thereby is achieved universality for calculations of heat gains resulting from solar radiation. By one part of the experiments and their evaluation is determined thickness of the standard single glass glazing. It is also determined proportional transmittance of solar radiation for certain multiwall polycarbonates, which are currently used as fillers of industrial skylights and production hall‘s window openings. From experiments resulting design is subjected to the simulation. Comparison of temperatures is shown for the time before the installation of designed solar shading and after the installation of the solar shading.
Creating a microclimate of an industrial building with high demands on its uniformity
Keywords: Sluneční radiace; tepelné zisky; tepelná zátěž; stínění; vícekomorový polykarbonát; poměrná propustnost; součinitel stínění; experimentální měření; simulace; Solar radiation; heat gains; heat load; solar shading; multiwall polycarbonate; proportional transmittance of solar radiation; shading coefficient; experimental measurements; simulation